English's Impact on Life as A Global Language: The Viewpoint of Teenagers - Sukri, Chintia Dewi; Nasution, Anggita Bella Afrilla (LingPoet: Journal of Linguistics and Literary Research, 2024)
Given that English is currently the most extensively utilized language globally, its importance cannot be dismissed or underestimated. This is because English is the most prevalent language spoken everywhere. Both consistent practice and patience are required in order to learn English. To advance in one's life, it is essential to have a working knowledge of the English language. It is the most important viewpoint of the contemporary world. Due to the prevalence of English as the primary language for communication worldwide, particularly among youth, this study focused on the impact that English has as a global language. The focus of this study was to explore what factors are contributing to why teenagers should learn English and the reasons why they had been learning English since earlier age. Teenagers were under the impression that all languages would eventually compete with English for the position of world language. It is anticipated that the future of English will provide us with a path to follow in how we conduct our operations in connection to the potential future of English. For millions of people all around the world, English is rapidly becoming an essential fundamental skill.